EFFECTS OF VARYING SETTINGS OF AN ISOLATED TRAFFIC SIGNAL IN BANDUNG - SURAJI, AJI
EFFECTS OF VARYING SETTINGS OF AN ISOLATED TRAFFIC SIGNAL IN BANDUNG, Aji Suraji, 1993, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. One important factor which influences delays and queue lengths at signalised intersections is the signal cycle time. This research was carried out at the signalised intersection of J1. Ahmad Yani and J1. Martadinata in Bandung. The data were recorded from video camera displays, and the data reduction and analysis were carried out in the laboratory. A computer program, called INTRA (INtersection TRaffic Analysis), was developed to support the data reduction and.analysis. A pilot study was carried out before varying the cycle time settings in order to test the method and obtain basic parameters for the research. Cycle time settings of 105 seconds, 120 seconds, 135 seconds and 150 seconds were selected. The measurement of queue lengths at various cycle time settings indicated that queue length increased roughly linearly with cycle time. A 15 second increase in cycle time gave an increase in queue length of approximately 2.4 vehicles for a flow band of 750-1000 pcu/h, and 2.6 vehicles for a flow band of 1000-1250 pcu/h. Analysis of the relationship between cycle time, delay and traffic demand indicated that delays were less at lower traffic demands, and that there was an optimum cycle time at which delays were minimised. This was about 115 seconds at lower flows and about 123 seconds at higher flows. When the results of the research were compared to those obtained from Webster's formula for optimum cycle time, differences were found between the formula and empirical results. The empirical results were therefore used to calibrate the constant terms in Webster's formula and gave an optimum cycle time relationship of Co = (2.2L+5.2)/(1-Y).